Electrochemical characterization of leached steel-making sludge - Langová, Šárka; Kostura, Bruno; Raška, Pavel; Matýsek, Dalibor; Novák, Vlastimil; Ritz, Michal; Krčmář, Jiří (Scientific reports, 2022)
In this work, the electrochemical properties of the leached sludge, magnetite and zinc ferrite were studied. Acetic acid was used as a leaching reagent because, in recent years, there has been a surge of interest in using zinc-containing materials as photocatalysts, with acetic acid finding application in their preparation. Various methodological approaches were used, but the best results were achieved with a combination of 1-3 h leaching in 0.01 M acetic acid with a solid/liquid ratio of 500. In this arrangement, zincite was almost completely removed from the sludge, while zinc ferrite and magnetite remained in the solid residue. Ex situ analyses of the main leaching products were performed by X-ray diffraction, infrared spectroscopy, and thermogravimetry. The electrochemical behaviour of solid residue and model systems, that are micromagnetite and zinc ferrite, was studied in alkaline media by means of modified carbon paste electrodes, cyclic voltammetry, and chronocoulometry, with a suitable potential window ranging from 0 to 1.5 V. In summary, a linear dependence of the anodic and cathodic peak height on the square root of the scan rate was found. The position of the anodic and cathodic peaks shifted slightly with scan rate, only at low rates, up to 25 mV/s, the individual peaks coincided. The electrochemical response suggested a quasireversible process.
Keywords: Carbon; Ferrosoferric Oxide; Sewage; zinek; elektrody; železité sloučeniny; elektrochemické techniky; Zinc; oxid železnato-železitý; ocel; odpadní vody; uhlík; Electrodes; Ferric Compounds; Steel; Electrochemical Techniques